Relationship between combination antiretroviral therapy regimens and diabetes mellitus-related comorbidities among HIV patients in Gaborone Botswana - Jose Gaby Tshikuka; Goabaone Rankgoane-Pono; Mgaywa Gilbert Mjungu Damas Magafu; Tiny Masupe; Mooketsi Molefi; Maurice Nsikungu-Kalukul; John Thato Tlhakanelo; Shimeles Genna Hamda; Vincent Setlhare (BMC, 2018)
Abstract Background Combination antiretroviral therapy (cARTs) regiments are known to prolong the recipients' life even though they are risk factors for diabetes mellitus-related comorbidities (DRCs). We sought to: (i) examine cART relationship with DRCs among patients attending HIV clinics in Gaborone, Botswana (which cART regimens are associated with shorter/longer time to the event), (ii) characterize patients' underlying biomedical and demographic risk factors of DRC and identify the most important, (iii) investigate survival of patients on different cART regimens in the presence of these risk factors. Methods Data from two major HIV clinics in Botswana were reviewed. Relationships between different cART regimens and DRCs were investigated among 531 recipients. Recipients' DRC risk factors were identified. Cox regression model was run. Unadjusted and adjusted hazard ratios were computed, and hazard and survival functions for different cART regimens were plotted. Results Major findings were: patients on second- and third-line cART were less likely to develop DRCs earlier than those on first-line cART. Patients with CD4 count ≤ 200 cells/mm3 at cART initiation were more likely to develop DRCs earlier than those who had CD4 count > 200 cells/mm3. Overweight patients at cART initiation had a higher risk of developing DRCs earlier than those who had normal body mass index. Males had a lower risk of developing DRCs earlier than females. Conclusion The risk of new onset of DRC among cART recipients is a function of the type of cART regimen, duration of exposure and patients' underlying biomedical and demographic DRC risk factors. The study has provided a survival model highlighting DRCs' significant prognostic factors to guide clinical care, policy and management of recipients of cARTs. Further studies in the same direction will likely improve the survival to the development of DRC of every cART recipient in this community.